Inadequate medication use in older adults - Oscanoa, Teodoro J (2005)
Objectives: To determine the prevalence of potentially inappropriate medication use and adverse drug-disease (defined by the Beers’ criteria) among hospitalized older adults and to identify predictors of this use. Material and Methods: A sample of 500 patients (mean age 75 years) admitted to the hospital between June 2002 and June 2003 was included in this analysis. Medication before, during or at discharge from hospitalization was considered for the present study. Results: On admission to the hospital 12,4% of the patients was taking a potentially inappropriate medication, 3,4% was given one medicine in the hospital, and 2,1% was prescribed one medication upon discharge. The most frequently potentially inappropriate medications prescribed on admission were diazepam, digoxin (>0,125 mg/day), iron supplements (>325 mg), chlorpheniramine, and amitriptyline. The prevalence of potentially adverse drug-disease interactions was 13,4% on admission, 5,4% during hospital stay and 4,2% on discharge. Statistical analysis with COOP/WONCA score showed that admission number of medications, number of diseases and pain were significantly associated with use of inappropriate medications. Conclusions: Our study revealed the existence of potentially inappropriate medications use among older adults in a Lima, Peru hospital inpatients. Polypharmacy, comorbidity and chronic pain were significantly associated with inappropriate medications use.